Visible-Light-Mediated Synthesis of Rutaecarpine Alkaloids through C–N Cross-Coupling Reaction - Chen, Dong; Li, Shiqing; Wang, Jinhua; Gou, Tiantian; Zhang, Linfeng; Wang, Guixia; Kong, Xiangfei (Synlett, 2021)
A visible-light-initiated cross-dehydrogenative-coupling amination is described, featuring metal- and photocatalyst-free, at room temperature, and using air as an oxidant. The reaction provides a facile approach for the synthesis of rutaecarpine and its derivatives. The substrates with electron-withdrawing groups give higher yields than those with electron-donating groups, but the substituent position has a negligible influence on the yield. Using binaphthyl-diyl hydrogen phosphate and dibenzyl phosphate as catalysts both deliver satisfying yields. This straightforward light-driven strategy might be applicable to the synthesis of quinazolinone derivatives.
Keywords: cross-dehydrogenation coupling; C–H amination; photochemistry; air oxidant; rutaecarpine; quinazolinone alkaloids